Placental Histomorphological and Radiological Changes and Their Association with Maternal Insulin Resistance in Gestational Diabetes Mellitus. - Naveed, Naveera; Shabbir, Aliya; Younis, Aleena; Javed, Najam-ul-Sehar; Memon, Roomi; Shahzad, Naeem (Journal of Neonatal Surgery, 2025)
Background: Gestational Diabetes Mellitus (GDM) is associated with maternal metabolic disturbances, particularly insulin resistance, leading to structural and functional alterations in the placenta. These changes can be evaluated through histomorphological and radiological assessment. Objective: To evaluate placental histomorphological and radiological changes in GDM and determine their association with maternal insulin resistance. Methods: This comparative cross-sectional study included 80 pregnant women (40 diagnosed with GDM and 40 normoglycemic controls). Maternal insulin resistance was assessed using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). Antenatal placental evaluation was performed using obstetric ultrasonography, assessing placental thickness, grading, and vascularity. Placental tissues were collected after delivery and examined histologically for villous immaturity, syncytial knots, fibrinoid necrosis, chorangiosis, and intervillous hemorrhage. Results: Radiological assessment revealed significantly increased placental thickness in the GDM group (4.6 ± 0.7 cm) compared to controls (3.8 ± 0.5 cm, p < 0.001). Advanced placental grading (Grade III before 37 weeks) was observed in 42.5% of GDM cases versus 12.5% of controls (p = 0.002). Increased placental vascularity on Doppler was noted in 60% of GDM cases compared to 22.5% in controls (p < 0.001). Histologically, syncytial knots were present in 72.5% of GDM placentae versus 32.5% of controls (p < 0.001), villous immaturity in 65% vs 27.5% (p = 0.002), chorangiosis in 55% vs 20% (p = 0.001), fibrinoid necrosis in 60% vs 25% (p = 0.003), and intervillous hemorrhage in 47.5% vs 17.5% (p = 0.004). Mean HOMA-IR levels were significantly higher in the GDM group (4.8 ± 1.2) compared to controls (2.1 ± 0.9, p < 0.001). A strong positive correlation was observed between HOMA-IR and placental thickness (r = 0.59), vascularity (r = 0.61), syncytial knot density (r = 0.62), and villous immaturity (r = 0.58), all statistically significant (p < 0.01). Conclusion: GDM is associated with significant radiological and histomorphological placental alterations, strongly correlated with maternal insulin resistance. Combined imaging and histological evaluation provides a comprehensive understanding of placental pathology in GDM and may aid in early identification of high-risk pregnancies and improved maternal-fetal outcomes..